Occurrence and Toxicity of Hydrocarbon Residues in Crab (Callinectes sapidus) from Contaminated Site - IA Ololade (Journal of Applied Sciences and Environmental Management, 2010)
To elucidate seasonal changes in hydrocarbons including polycyclic aromatic hydrocarbons (PAHs) due to oil spill, tissues of blue crab (Callinectes sapidus) were investigated. Total petroleum hydrocarbons (n-alkanes) concentrations ranged from 0.17-0.32ìg/gdw and 0.28-0.62ìg/gdw during the dry and wet seasons respectively. The tissues accumulate a complex spectrum dominated by heavier hydrocarbons, alkylsubstituted and PAHs. The impact of biogenic contribution through dietary uptake was related to the elevated levels, particularly of the PAHs. Studies of other site specific, resident organism are recommended in order to be able to establish the extent of toxicity.